2019
DOI: 10.11591/ijpeds.v10.i4.pp2157-2164
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency investigation of SS and SP compensation topologies for wireless power transfer

Abstract: <span>Wireless power transfer (WPT) using inductive and resonant coupling has been widely explored in recent years for ease and safety over conventional cable charging systems. The efficiency of WPT systems is reducing drastically due to an increase in air-gaps and misalignment between transmitter (Tx) and receiver (Rx). Many circuit topologies have been analyzed to improve the efficiency of WPT system based on symmetrical coils. However, the circuit topologies have not been studied widely for unsymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…This is more related to the quality factor of the components themselves and the choice of the more favorable operation point, which may be different for each topology, similarly to what happens with the output power itself. This is exemplified by a case study [96] where the SP efficiency is reported to be better than that of the SS-compensation when lower magnetic coupling coefficients, resulting from asymmetry in the coils, are observed, but worse otherwise.…”
Section: Other Circuit Compensation Topologiesmentioning
confidence: 93%
“…This is more related to the quality factor of the components themselves and the choice of the more favorable operation point, which may be different for each topology, similarly to what happens with the output power itself. This is exemplified by a case study [96] where the SP efficiency is reported to be better than that of the SS-compensation when lower magnetic coupling coefficients, resulting from asymmetry in the coils, are observed, but worse otherwise.…”
Section: Other Circuit Compensation Topologiesmentioning
confidence: 93%
“…We used SP topology to simplify the battery management system. Since SP is more efficient than SS when the Tx coil is bigger than Rx, series capacitor (C s ) and parallel capacitor (C p ) were connected to the Tx and Rx coil, respectively [33]. The values of primary and secondary capacitors are calculated using Equation (2).…”
Section: Wireless Power Transfer (Wpt) Systemmentioning
confidence: 99%
“…If the inductance for a greater transfer distance is increased, the efficiency will decrease due to a higher loss of parasite resistance and an increase in the number of windings. [25].…”
Section: Transmitter and Receiver Coilsmentioning
confidence: 99%